Separatist Movement and Maintaining the Integrity of the Indonesian People's State - Siregar, Evi Riani (International Journal of Students Education, 2024)
Ideology in life in a country can be interpreted as the majority agreement of citizens about the basic values that they want to realize through the formation of a country. In this case, it is often referred to as a philosophical background or worldview, namely the deepest thoughts and desires of citizens regarding the establishment of citizens. Pancasila is a state philosophy that was born as a shared ideal of the entire Indonesian nation. Ideology comes from the word Idea which means ideas, basic ideas or ideals and logos which means knowledge, science and understanding. Ideology is a system of thought or views that regulates the way humans understand and approach cultural, social, political, and economic issues. Ideology and the establishment of the Indonesian nation, as living beings who believe in God Almighty and are aware of their nature as personal and social beings. As stated in the opening of the 1945 Constitution, the Unitary State of the Republic of Indonesia (NKRI) respects all efforts of the nation to describe and regulate human rights in accordance with their respective value systems and ideologies. In this case, Indonesia as a nation must uphold human rights based on Pancasila as the state ideology in order to exist as a unitary state of the Republic of Indonesia.